Adherence and quality of care in IBD. (1st November 2016) - Bager, Palle; Julsgaard, Mette; Vestergaard, Thea; Christensen, Lisbet Ambrosius; Dahlerup, Jens Frederik
Abstract: Objective: In inflammatory bowel disease (IBD), adherence to both medical treatment and other aspects of care has a substantial impact on the course of the disease. Most studies of medical adherence have reported that 30–45% of patients with IBD were non-adherent. Our study aimed to investigate the different aspects of adherence and to identify predictors of non-adherence, including the quality of care, for outpatients with IBD. Materials and methods: An anonymous electronic questionnaire was used to investigate different aspects of adherence, the quality of care, patient involvement and shared decision making among 377 IBD outpatients. Results : Three hundred (80%) filled in the questionnaire. The overall adherence rate was 93%. Young age (< 35 years old) and smoking were significantly associated with non-adherence (prevalence odds ratio (POR) 2.98, 95% CI 1.04–8.52, p  < 0.05 and POR 3.88, 95% CI 1.36–11.05, p  < 0.05, respectively). The lowest medical adherence rates were found for 5-ASA and topical treatments among patients with inactive disease. A large majority of patients stated that treatment strategies were agreed upon as a shared decision between the patient and the health care professionals. Conclusions: Predictors for non-adherence were young age and smoking. High adherence rates could be explained by a high patient satisfaction and a high degree of shared decision making.